Cognitive function in clinical burnout: A systematic review and meta-analysis. Issue 1 (2nd January 2022) - Gavelin, Hanna M.; Domellöf, Magdalena E.; Åström, Elisabeth; Nelson, Andreas; Launder, Nathalie H.; Neely, Anna Stigsdotter; Lampit, Amit
ABSTRACT: Clinical burnout has been associated with impaired cognitive functioning; however, inconsistent findings have been reported regarding the pattern and magnitude of cognitive deficits. The aim of this systematic review and multivariate meta-analysis was to assess cognitive function in clinical burnout as compared to healthy controls and identify the pattern and severity of cognitive dysfunction across cognitive domains. We identified 17 studies encompassing 730 patients with clinical burnout and 649 healthy controls. Clinical burnout was associated with impaired performance in episodic memory ( g = −0.36, 95% CI −0.57 to −0.15), short-term and working memory ( g = −0.36, 95% CI −0.52 to −0.20), executive function ( g = −0.39, 95% CI −0.55 to −0.23), attention and processing speed ( g = −0.43, 95% CI −0.57 to −0.29) and fluency ( g = −0.53, 95% CI −1.04 to −0.03). There were no differences between patients and controls in crystallized ( k = 6 studies) and visuospatial abilities ( k = 4). Our findings suggest that clinical burnout is associated with cognitive impairment across multiple cognitive domains. Cognitive dysfunction needs to be considered in the clinical and occupational health management of burnout to optimise rehabilitation and support return-to-work.